Of the laws of ecclesiastical polity - Hooker, Richard ((Everyman's library, 1907)
CONTENTS.-v.1. Introduction. Sermon on the certainty and perpetuity of faith in the elect. A learned discourse of justification. A preface. Of the laws of ecclesiastical polity: First-fourth book.-v.2. Dedicatory epistle to Archbishop Whitgift. Of the laws of ecclesiastical polity: The fifth book. Appendix I: Fragments of answer to a "Christian letter". Appendix II: George Cranmer's letter.